Preparation, characterization, antioxidant properties of novel Schiff bases including 5-chloroisatin-thiocarbohydrazone - Bakır, Temel Kan; Lawag, Jamal Basir (Springer Science and Business Media LLC, 2020)
Thanks to its pharmaceutical properties, the Schiff group of isatin has recently had a wide range of uses. In this study, seven new Schiff bases of isatin and its derivatives were prepared from thiocarbohydrazide, isatin and substituted aldehydes in the presence of ethanol under reflux. The chemical structures of the products were confirmed by 1H NMR, 13C NMR, IR and elemental analysis. The in vitro antioxidant features of all the compounds were evaluated by 1,1-diphenyl-2-picrylhydrazyl free radical scavenging method. The antioxidant effect was evaluated separately in two different stages: monosubstituted products synthesized with aldehyde groups and disubstituted products bound with isatin group. Accordingly, the compounds 3 and 4 showed the highest antioxidant activity and the isatin group suppressed the antioxidant effect of the disubstituted Schiff bases products.
Keywords: 3. Good health